PENGARUH PINJAMAN MODAL KERJA DAN KEMITRAAN TERHADAP PENDAPATAN USAHA (STUDI KASUS PADA UKM ANGGOTA KOPERASI SIMPAN PINJAM BHAYANGKARA KEDIRI) - Reka Sitha Devi Sunarno; Hari Susanta Nugraha (Universitas Diponegoro, 2020)
The Bhayangkara Kediri Savings and Credit Cooperative is a credit cooperative whose activities are only centered on the form of savings and loans from members. In an effort to provide member welfare, the Bhayangkara Savings and Loan Cooperative provides services that can support the needs of members including developing Small and Medium Enterprises (SMEs) by increasing business revenues. This study aims to determine how the influence of working capital loans and participation in partnerships on business income in UKM members of the Bhayangkara Kediri savings and loan cooperative. The method used in this study uses quantitative research with explanatory research type with a census of 30 respondents. Data collection using a questionnaire with a Likert measurement scale. Data analysis methods used are validity and reliability test, correlation coefficient (R), regression test, coefficient of determination (R2), significance of t test and F test with SPSS 21 application. The results showed a positive and significant effect between working capital loans and partnerships on business income in UKM members of Bhayangkara Kediri savings and loan cooperatives, both partially and simultaneously. Working capital loan variable has the biggest influence on business income which is 27.8% while the Partnership is 32.5%. Member SMEs in managing their businesses need to obtain working capital loans. Participation in the Partnership can also increase business in an effort to develop a business.